Super-resolved local recruitment of CLDN5 to filtration slits implicates a direct relationship with podocyte foot process effacement - Tesch, Florian; Siegerist, Florian; Hay, Eleonora; Artelt, Nadine; Daniel, Christoph; Amann, Kerstin Ute; Zimmermann, Uwe; Kavvadas, Panagiotis; Grisk, Olaf; Chadjichristos, Christos; Endlich, Karlhans; Chatziantoniou, Christos; et al. (Journal of Cellular and Molecular Medicine, 2021)
Under healthy conditions, foot processes of neighbouring podocytes are interdigitating and connected by an electron-dense slit diaphragm. Besides slit diaphragm proteins, typical adherens junction proteins are also found to be expressed at this cell-cell junction. It is therefore considered as a highly specialized type of adherens junction. During podocyte injury, podocyte foot processes lose their characteristic 3D structure and the filtration slits typical meandering structure gets linearized. It is still under debate how this change of structure leads to the phenomenon of proteinuria. Using super-resolution 3D-structured illumination microscopy, we observed a spatially restricted up-regulation of the tight junction protein claudin-5 (CLDN5) in areas where podocyte processes of patients suffering from minimal change disease (MCD), focal and segmental glomerulosclerosis (FSGS) as well as in murine nephrotoxic serum (NTS) nephritis and uninephrectomy DOCA-salt hypertension models, were locally injured. CLDN5/nephrin ratios in human glomerulopathies and NTS-treated mice were significantly higher compared to controls. In patients, the CLDN5/nephrin ratio is significantly correlated with the filtration slit density as a foot process effacement marker, confirming a direct association of local CLDN5 up-regulation in injured foot processes. Moreover, CLDN5 up-regulation was observed in some areas of high filtration slit density, suggesting that CLND5 up-regulation preceded the changes of foot processes. Therefore, CLDN5 could serve as a biomarker predicting early foot process effacement.
CRIS-Team Scopus Importer:2021-07-02
Keywords: 3D-structured illumination microscopy; Claudin-5; foot process effacement; glomerulosclerosis; podocyte; tight junction proteins